A STUDY OF THEATER OF THE ABSURD THROUGH THE CANNON OF RELEVANCE THEORY (Contemporary Journal of Social Science Review, 2024)
Dan Sperber and Deirdre presented the relevance theory in 2012, which was the advanced version of Gricean Maxims. As per the theory, the language patterns used in any speech, dialogue, or communication has a specific relevance when inferred. It is considered as a psychological model as it uses cognitive approaches to study the communication stances. Hence, the research aims at finding the meaning in Absurd Theater by using relevance theory. For this purpose, the researchers study various works of Harold Pinter, and Becket and the dialogues are interpreted through the theory. The study has two hypotheses regarding illogical premises and the flouting of relevance maxim and in both cases relevance theory can solve the puzzle by putting meaning in illogical premises and by adding the piece of non-dualism in the case of flouting and opting out. In this way, the study has proved that the writings of absurd theater have a conception of non-dualism, no absolute truth in the writings of theater, Gricean maxims cannot help study the dialogues of absurdists, and the last one is about the role of non-dualism behind the writings of absurd theater. Besides that, the study also proved that Taoism is very related to the writings of Theater of the Absurd. The study recommends that other lineage of absurd theater can also be possible through finding its relations with different philosophical thoughts.